Challenges Faced by PNP in Resolving Cybercrime Cases - Fajardo, Maribel B.; Abragon, Mario N.; Abuan, Lezeil Lopez; Hinlayagan, Justeofino M.; Marmol, Deodennis Joy; Contreras, Anne B.; Basbas Jr., Rogelio; Villa, Elizabeth B. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
The research examined the correlation between the level of chal-lenges faced by the PNP-ACG and various demographic factors. Addi-tionally, it examined the specific components of cybercrime offenses, which include offenses against the confidentiality, integrity, and availability of computer data and systems, as well as offenses related to computers, content, and other areas.The findings indicated that the PNP-ACG faced roughly the same level of challenges as other law enforcement groups in the region. In-terestingly, demographic factors such as age, length of service, educa-tional attainment, and training attendance did not significantly affect the level of obstacles faced by the PNP-ACG personnel.Moreover, the study revealed a significant relationship between the number of problems the PNP-ACG had and the types of privacy, honesty, and other crimes that happened during their digital forensic investigations and operations.These findings suggest that the challenges faced by the PNP-ACG are more systemic in nature and not primarily driven by individual or demographic characteristics. The study ends with suggestions for how to improve the PNP-ACG in the region by doing a full organiza-tional assessment, creating a strong digital forensic management sys-tem, running programs to build people's skills, and working together with other groups to deal with the problems that were found.